2017
DOI: 10.1186/s12711-016-0279-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of alternative approaches to single-trait genomic prediction using genotyped and non-genotyped Hanwoo beef cattle

Abstract: BackgroundGenomic predictions from BayesA and BayesB use training data that include animals with both phenotypes and genotypes. Single-step methodologies allow additional information from non-genotyped relatives to be included in the analysis. The single-step genomic best linear unbiased prediction (SSGBLUP) method uses a relationship matrix computed from marker and pedigree information, in which missing genotypes are imputed implicitly. Single-step Bayesian regression (SSBR) extends SSGBLUP to BayesB-like mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 20 publications
4
40
2
4
Order By: Relevance
“…To reduce the bias of genomic predictions, future research should be done using, for example, the single-step Bayesian regression method (ssBR; Fernando et al, 2014Fernando et al, , 2016, which considers different assumptions for the effects of markers, unlike ssGBLUP. Lee et al (2017) comparing different single-step methodologies concluded that in general the results were similar between ssGBLUP and ssBR; however, the ssBR was superior when the trait is associated with QTL with large effects.…”
Section: Blending Of Traditional Information and Genomic Predictionsmentioning
confidence: 98%
“…To reduce the bias of genomic predictions, future research should be done using, for example, the single-step Bayesian regression method (ssBR; Fernando et al, 2014Fernando et al, , 2016, which considers different assumptions for the effects of markers, unlike ssGBLUP. Lee et al (2017) comparing different single-step methodologies concluded that in general the results were similar between ssGBLUP and ssBR; however, the ssBR was superior when the trait is associated with QTL with large effects.…”
Section: Blending Of Traditional Information and Genomic Predictionsmentioning
confidence: 98%
“…The direct genomic values obtained from these models can then be blended with BLUP breeding values. Alternatively, genomically enhanced breeding values could be obtained directly with a Bayesian single-step method (Lee et al, 2017).…”
Section: Achieving Genetic Gainmentioning
confidence: 99%
“…As this model is able to use geneological information and genotype information simultaneously, the accuracies of ssGBLUP and improvements thereof are usually at least as high as for any other method (Legarra et al, 2014). Exceptions are traits that are predominantly affected by few QTL with large effect (Lee et al, 2017), in which case direct genomic values are more appropriately estimated by a Bayesian SNP method or a Bayesian single-step method.…”
Section: Achieving Genetic Gainmentioning
confidence: 99%
“…However, it is still unclear how different components such as LD between markers and QTL, in addition to population structure, contribute to GEBV accuracy in the single-step analysis. Furthermore, very few studies to date have investigated the relative performance of various single-step Bayesian models (Lee et al 2017). Therefore, by using a simulation study, we investigated the contributions of GEBV accuracy in the single-step analysis in this study.…”
Section: Introductionmentioning
confidence: 99%